Interactions between lymphocytes, macrophages, and central nervous system cells - Couraud Po
Brain has often been considered as an "immunologically privileged organ," not normally accessible to leukocyte traffic, at least in part because of the presence of the blood-brain barrier, constituted by a specialized microvasculature and surrounding astrocytes, which restricts the exchanges between blood and brain. However, more recent studies have revealed that activated leukocytes can cross into the CNS, at very low levels under normal conditions, in much higher numbers during neuropathological disorders like multiple sclerosis or retroviral infection, and, within brain parenchyma, interact with CNS cells. The present review will thus highlight the multidirectional communication network, based on adhesion molecule expression and cytokine production, which appears in such situations between infiltrated leukocytes, brain microvessel endothelial cells, macroglia (including astrocytes and oligodendrocytes), microglial cells and neurons.
Keywords: BLOOD-BRAIN BARRIER; GLIAL CELLS CELL ADHESIÓN; DEMYELINATING DISEASE